A Qualitative Analysis of Women's Short Accounts of Labour and Birth in a Western Australian Public Tertiary Hospital - Bayes, Sara; Fenwick, Jennifer; Hauck, Yvonne (Elsevier, 2008)
This paper reports the findings of the postnatal qualitative arm of a larger study,which investigated women's prenatal and postnatal levels of childbirth fear. Women's expectations and experiences of labour and birth in a Western Australian public tertiary hospital were identified following thematic analysis of short written accounts from 141 participants who had given birth in the previous 6 to 14 weeks. Four major categories emerged to describe features and mediating factors in the trajectory of childbirth and the early puerperium "Anticipating Labour and Birth", "Labour and birth Depicted", "Mediating Factors and their consequences" and "Evaluating, Resolving, and Looking Ahead" portray women's comparative reflections on expectations and realities of birth, on mediating influences, and on moving on from their experience. These findings will provide maternity care professionals with insight into the personal and environmental features of the childbirth setting which colours women's recollections. Being aware of what women value during labour and birth will reinforce the need for professionals to provide care using a mindful approach that considers the potential psychological, emotional and behavioural implications of events.